Suffering and Depersonalization in Hospitals: the challenges of the hospital psychologist (Research, Society and Development, 2022)
The suffering and depersonalization in hospitals result in a series of emotional disorganizations in the hospitalized subject, as well as in their families and in the health team. With the aim of investigating the contributions of the hospital psychologist to minimize the suffering and depersonalization of the patient in the hospital environment, the study in question is characterized as an integrative bibliographical research and proposes an investigation into the psychic aspects involved in the illness processes and hospitalization. From the data collected in the scientific literature, were put in evidence care strategies that promote well-being, evolution of the clinical condition and the minimization of suffering and depersonalization arising from hospitalization could be evidenced. The analyzed studies also point out that the role of the hospital psychologist can contribute to the preservation of the patient's subjectivity, through, above all, the reception and an attentive, welcoming and ethical listening directed to the patient and their caregiver. Thus, it is concluded that the actions of the psychologist inserted in the hospitalization routine can contribute to the reduction of psychological damage resulting from illness and hospitalization, as well as to help the multidisciplinary team involved in health care processes. The results obtained in this study aim to promote the expansion of knowledge about the psychosocial impacts resulting from illness and the hospitalization process, in addition to offering contributions to the practice of humanized care.